P51 Time to start testing for latent TB infection(LTBI)- a quality improvement project. (16th June 2022) - Forsyth, Sophie; Subuloluwa, Tolulope; Lwin, Myat; Daniel, Jessica
Abstract : Introduction: 2018 BHIVA Tuberculosis (TB) guidelines recommend testing people living with HIV (PLWH) from countries with high and medium TB incidence for LTBI and from low-incidence countries if they have additional TB risk factors. We had not yet introduced this in our HIV service when 5 of our patients were diagnosed with TB between February 2020 and May 2021. Methods: GUM and hospital notes of the 5 PLWH diagnosed with TB were reviewed. PLWH suitable for LTBI testing were also identified. Results: Of the PLWH diagnosed with TB, 2 were from India, 1 from Kenya and 2 from Zimbabwe. 4 had been diagnosed with HIV for at least 2 years and had CD4 counts over 350 on effective antiretroviral treatment. 3 had TB lymphadenitis, 1 pulmonary TB and 1 diagnosed from bone marrow. All 5 patients required hospital admission due to complications of treatment and co-morbidities. We identified 165/320 PLWH eligible for LTBI testing in our cohort. We procured a provider and secured the funding to offer LTBI testing. Discussion: PLWH are at increased risk of progressing to active TB especially if they have low CD4 counts or originate from countries with high TB incidence. Had our patients been offered LTBI testing and treatment at HIV diagnosis they may have not gone on to develop active TB although 3 of them were diagnosed with HIV at least 7 years earlier. We are now testing all PLWH in our care with risk factors and will repeat testing following travel to high-incidence countries